'Romantic Piano' and 'Sleazy Saxophone': Categories and Stereotypes in Library Music Catalogues. Issue 1 (1st July 2020) - DURAND, JÚLIA
Abstract : Library music is currently used in countless audio-visual contexts, from documentaries to YouTube videos. It has become an essential resource for video editors and a relevant source of revenue for composers. Although this pre-existing music is rapidly gaining significance and more varied uses, it still has a reputation in musicological scholarship of being uninteresting and stereotyped. By organising their music in neatly labelled drawers, library music catalogues appear to present a vision of sonorities closely aligned with narratives and images. However, the very same piece may sometimes be heard in widely different contexts. Drawing from an examination of the catalogues of two European library music companies, Audio Network and Cézame, as well as from interviews with composers and music consultants, I focus on how the categories, titles, and descriptions of library music tracks play a relevant role, even a decisive element, in their composition and subsequent use. Taking as examples such categories as 'romantic' and 'erotic', it is possible to show that these texts reflect and, simultaneously, reinforce widespread narrative and musical conventions in cinema and television. Such classifications potentially contribute to negative views about library music, by making apparent its fundamental organisation around standardised categories and recurrent musical clichés.